2015
DOI: 10.1111/edt.12170
|View full text |Cite
|
Sign up to set email alerts
|

Timing of maxillofacial–oral injuries in an individual of the ancient city of Herculaneum (79 AD, Naples, Italy): a case report

Abstract: These results are an illustration of how dental anthropology and forensic approaches can be applied with great benefit to archaeological skeletal remains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 81 publications
0
2
0
1
Order By: Relevance
“…Teeth are known for being the hardest and most durable and resistant biological remains, as these can survive a variety of destructive effects caused by chemical, physical, mechanical and thermal variations (Fereira et al 2008;Schmidt 2008;Viciano et al 2012;Viciano et al 2015a). Sex estimation from dental characteristics is primarily based on comparisons of dental dimensions (odontometrics) between males and females, and numerous studies have identified sex differences in such metric characteristics of the permanent dentition (Adams & Pilloud 2019;De Angelis et al 2015;Peckmann et al 2015;Tardivo et al 2015;Zorba et al 2012;Viciano et al 2011;Viciano et al 2013;Viciano et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Teeth are known for being the hardest and most durable and resistant biological remains, as these can survive a variety of destructive effects caused by chemical, physical, mechanical and thermal variations (Fereira et al 2008;Schmidt 2008;Viciano et al 2012;Viciano et al 2015a). Sex estimation from dental characteristics is primarily based on comparisons of dental dimensions (odontometrics) between males and females, and numerous studies have identified sex differences in such metric characteristics of the permanent dentition (Adams & Pilloud 2019;De Angelis et al 2015;Peckmann et al 2015;Tardivo et al 2015;Zorba et al 2012;Viciano et al 2011;Viciano et al 2013;Viciano et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the palaeobiological studies carried out on the bone and dental human remains of the victims of the eruption has allowed the obtention of useful information not only to understand the habits and lifestyle of the ancient inhabitants, but also the status of health and diseases with which the general population was affected (e.g., [ 41 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]). Although bone and dental human remains constitute the primary source through which it is possible to derive direct information on the diseases suffered by the ancient inhabitants, osteological remains from animal assemblages are no less important to provide data that can help to elucidate the close coexistence and animal–human interaction, and the animal-related infections transmitted to humans in the community.…”
Section: Historical Background Of the Roman Cities Of Pompeii And Herculaneummentioning
confidence: 99%
“…ej. : D'Anastasio et al, 2013;Viciano et al, 2012Viciano et al, , 2015aViciano et al, , 2015b, pero también incluye dientes de otras especies animales, entre los que se encuentran nueve especímenes de C. megalodon. Los dientes de megalodonte se presentan en buen estado de conservación, de modo que su descripción y puesta en conocimiento a la comunidad científica puede complementar las colecciones ya existentes y contribuir a los estudios sobre las relaciones filogenéticas de C. megalodon con otros tiburones extintos y modernos y su ecología.…”
Section: Introductionunclassified